Incidence of Carcinoma Prostate in Transurethral Resection Specimen in a Teaching Hospital of Nepal - Thapa, Neeraj; Shris, Sachin; Pokharel, Nabin; Tambay, Yashwant Gajanan; Kher, Yashwant Ramakrishan; Acharya, Sumnima (Journal of Lumbini Medical College, 2017)
Introduction: As suggested through several autopsy studies there is a high prevalence of latent prostate cancer in the population. A much smaller proportion of prostate cancer is detected because of clinical symptoms. This study was done to identify the rates of incidentally detected prostate cancer in patients undergoing surgical management of Benign Prostatic Hyperplasia (BPH) in our centre. Methods: A retrospective review was done on all transurethral resections of the prostate (TURP) cases from May 2014 to May 2015 at a single tertiary care institution. One hundred and three men, aged 40 to 88 year, underwent TURP and their specimens were sent for the histopathological analysis.Results: Five (4.85%) patients were diagnosed with the prostate cancer. All the five patients had Gleason score of seven or more. Two patients had moderately differentiated adenocarcinoma with Gleason score of seven. Three patients had poorly differentiated adenocarcinoma with Gleason score of eight or above. The Prostate cancer was seen only in the age group above 65 years but it was not statistically significant.Conclusion: Our series demonstrated that 4.85% of patients had latent prostate cancer. It occurs mainly in men above 65 years of age though this was not statistically significant.J. Lumbini. Med. Coll. Vol 4, No 2, July-Dec 2016, Page: 77-79DOI: https://doi.org/10.22502/jlmc.v4i2.95